The Mcgregor Pedicled Groin Flap for Complex Hand Soft-Tissue Defects: Anatomy, Surgical Technique, Indications, And Reconstructive Outcomes - Marisela Silva García; Cristian Sandoval Cervantes (International Journal of Medical Science and Clinical Research Studies, 2026)
Complex soft-tissue defects of the hand remain among the most demanding challenges in reconstructive surgery because successful treatment requires durable coverage, protection of exposed structures, preservation of tendon glide, restoration of mobility, and acceptable donor-site morbidity. Although microsurgical free tissue transfer and perforator flap techniques have expanded the reconstructive armamentarium, the McGregor pedicled groin flap remains a reliable, technically accessible, and versatile option for selected hand, digital, wrist, and distal forearm defects. Based primarily on the superficial circumflex iliac artery (SCIA) vascular territory, the flap provides robust soft-tissue coverage without requiring microvascular anastomosis. This makes it particularly useful in traumatic injuries, degloving wounds, exposed tendons or bone, contaminated wounds, resource-limited settings, and patients who are poor candidates for prolonged microsurgery. Its limitations include staged division, temporary immobilization, bulkiness, stiffness risk, donor-site morbidity, and the need for structured postoperative rehabilitation. This review summarizes contemporary evidence regarding the anatomical basis, indications, surgical technique, postoperative care, outcomes, complications, and modern role of the McGregor pedicled groin flap in hand reconstruction. A modern reconstructive approach should not consider the groin flap obsolete; rather, it should define its optimal role within a patient-centered algorithm that balances defect characteristics, available expertise, institutional resources, functional goals, and rehabilitation capacity.